The Prevalence of Distress and Depression among Women in Rural Sichuan Province - Qiu, Peiyuan (PLoS One, 2016)
BACKGROUND: In this paper, we report findings regarding the prevalence of expressed distress and depressive conditions among women living in a rural region of Sichuan Province. As well, we know of no data among women in rural China that examine whether “depression,” as categorically defined in classifications such as the DSM, adequately captures the expressed distress and symptomatic complaints of women in rural China. METHODS: A multistage sampling method was employed to recruit the target population. The Center for Epidemiologic Studies Depression Scale (CES-D) was used to measure distress symptoms, and MINI International Neuropsychiatric Interview (MINI) was employed to determine the prevalence of diagnosable depression and other disorders. RESULTS: Among 1898 rural women, 12.4% (236) scored ≥16 on the CES-D, indicative of distress, and a subset of 7.7% (146) had scores ≥21, highly suggestive of a clinically significant disorder. We found that 49.8% women with ≥16 CES-D score were identified as showing features consistent with a current major depressive episode (MDE) vs. 1.9% in a sample of randomly selected women with <16 CES-D score. Among respondents, 30 of 84 (35.7%) scoring 16–20 and 83 of 143 (58.0%) scoring ≥21 reported symptoms consistent with MDE. 25.1% of women with a positive CES-D score did not describe symptoms consistent with any DSM-IV disorder. CONCLUSIONS: We found a higher portion of women reporting significant distress than previously described. Among them, there was a clear gradient, such that 41.7% of women with moderate distress did not have a psychiatric diagnosis, and even among those with more severe symptoms, 15.4% did not manifest a DSM-specific psychiatric condition.